TEACHERS’ PERSPECTIVE ON INTEL CLASSMATE PC AS AN INSTRUCTIONAL TOOL - Abuhmaid, Atef (European Scientific Journal, ESJ, 2013)
The debate over the integration of technology in education has become more focused on the ways in which education can contend with new technologies. Numerous research has pointed to the effectiveness of various technologies in improving educational practices and outcomes which has shifted the focus from the “whether” to “how”. Nevertheless, the rapid development of new technologies may leave educational institutions ponder on the “how” issue. One laptop per child initiatives are one of the latest trends in the integration of new technologies in educational contexts. The current study investigates teachers’ perspective at Alhofaz Academy, in Jordan, regarding their attempt to replace the traditional textbook with Intel Classmate PCs. The study utilized a questionnaire to capture teachers’ perspectives on the school’s implementation of the initiative and its impact on students’ three learning domains: cognitive, affective, and psychomotor. The findings of the study showed that despite the positive attitudes teachers held towards the Classmate, they criticized the school’s approach of adopting and implementing the initiative.